Influence of transcutaneous spinal stimulation on human LTP-like pain amplification. A randomized, double-blind study in volunteers. Issue 8 (August 2017) - Schweizer, L.M.; Zahn, P.K.; Pogatzki-Zahn, E.M.; Magerl, W.; Tegenthoff, M.; Meyer-Frießem, C.H.
Highlights: TsDCS had no effects on pain perception associated with LTP-like pain in healthies. TsDCS was not able of preventing sensitization or alleviating pain after sensitization. TsDCS likely has no effect on the TRPV1-positive C and A fibers associated with hyperalgesia. Abstract: Objective: Transcutaneous spinal direct current stimulation (tsDCS) has been proven to affect nociceptive signal processing. We designed a randomized, double-blind, cross-over study to investigate whether tsDCS applied before or after inducing long-term potentiation-(LTP)-like hyperalgesia may decrease nociceptive sensitivity. Methods: In healthy volunteers, tsDCS (2.5 mA, 15 min) was applied to the thoracic spine prior ( n  = 14) or immediately following ( n  = 12) electrical high-frequency stimulation (HFS) to the thigh, inducing hyperalgesia. Mechanical and electrical perception were assessed before HFS stimulation and at three time points following HFS stimulation (all within 90 min of HFS). Subjects took part in three separate sessions to test effects of anodal, cathodal, or sham tsDCS. Results: Within 60 min HFS led to unilateral changes on the conditioned side: mechanical pain thresholds tended to decrease and electrical detection thresholds significantly decreased ( p  < 0.001); pain ratings measured using the numerical rating scale (NRS) increased for electrical stimuli ( p  < 0.01) and two categories of mechanical stimuli ("Light(8–64 mN)": p  = ns; "Heavy(128–512 mN)": p  < 0.01). Irrespective of stimulation order or polarity, tsDCS could not influence nociceptive sensitivity. Conclusion: Hyperalgesia was adequately induced, but tsDCS had no effect on HFS-induced sensitization. Significance: While tsDCS has been shown to affect pain measures, our results suggest irrespective of time of stimulation or polarity that tsDCS may be less effective in modulating pain in a sensitized state in healthy subjects.